Variational eigenvalues of the fractional g -Laplacian - Bahrouni, Sabri (2022)
In the present work we study existence of sequences of variational eigenvalues to non-local non-standard growth problems ruled by the fractional g-Laplacian operator with different boundary conditions (Dirichlet, Neumann and Robin). Due to the non-homogeneous nature of the operator several drawbacks must be overcome, leading to some results that contrast with the case of power functions.